UNDERSTANDING COMPLEXITY WITHIN ENERGY INFRASTRUCTURE DELIVERY SYSTEMS IN DEVELOPING COUNTRIES: ADOPTING A VIABLE SYSTEMS APPROACH - B.O. Awuzie; P. McDermott (Journal of Construction Project Management and Innovation)
Infrastructure delivery systems involve high complexity. This stems from numerous factors: a diverse range of skilled professionals, diverse cultural affiliations, incomplete contracts and complex contractual relationships among stakeholders, government policies, finance and regulatory issues, and high levels of asset specificity. The degree of complexity is enhanced in projects requiring high levels of specialization. Energy infrastructure projects can be described as possessing a relatively high degree of complexity. The ability to understand and manage such complexity directly affects project performance. Previous studies into the failure of most of these projects have traced project failures to several factors such as corruption, lack of transparency in the procurement process, lack of proper regulatory frameworks, and lack of political willpower. Surprisingly, few studies have attempted to spearhead a concise understanding of the inherent complexities in delivery systems. This paper attempts to contribute to the literature on project delivery process and its inherent complexities. This study proposes a viable systems model approach to understanding complexities in energy infrastructure delivery systems in developing countries. This is based upon the premise that a system must be understood properly to enable effective diagnosis. It argues that whereas the aforementioned factors adversely affect the performance of the infrastructure projects, a better understanding of the delivery process would allow for timely and appropriate solutions to be proffered. The viable systems model is premised on the concept of systems thinking and cybernetics-science of communication and control. It has proven effective in diagnosing organizations. It is hoped that this study, which forms part of an on-going PhD study, would elicit further discourse in the application of the viable systems model in diagnosing and re-designing infrastructure delivery systems within the energy sector of developing economies.